ANALYSIS OF FARMERS INTENTION TO IMPLEMENT GOOD AGRICULTURAL PRACTICES ON COCOA FARMS BY USING THEORY OF PLANNED BEHAVIOR - Awaluddin Awaluddin; Nurlita Pertiwi; Bakhrani A. Rauf; Faizal Amir; Yulis Sayang; Muhammad Azwar (International Conference on Social and Islamic Studies, 2021)
The development of the concept of sustainable agriculture in the cocoa farming system is the conception of Good Agricultural Practices (GAP) on Cocoa. The purpose of this research is to identify the factors that influence farmers' intentions to implement Good Agricultural Practices on cocoa in Bupon Sub District, Luwu Regency. Previous studies on the adoption of agricultural innovation often consider socio economic characteristics and overlook underlying psychological factors influencing farmers’ behavioral intention. This study's framework is based on Ajzen's theory of planned behavior (TPB) to evaluate variables antecedent to farmers' intention to implement Good Agricultural Practices on cocoa, such as attitude, subjective norm, knowledge, and perceived behavior control. Using a self-administered questionnaire, a quantitative research approach was used to collect responses from 130 farmers from three villages in the Bupon Sub District of Luwu Regency. According to the findings, TPB antecedent variables: attitudes, subjective norms, and perceived behavioral control have significant effect and positively correlated to the farmer’s intention to Implement Good Agricultural Practices (GAP) on study area.